Changes in the Intraluminal Protein Digestion of Pancreatic Duct-Ligated Rats - HAGIHIRA, Hiroshi; MINAMI, Hisanori; KONDOH, Maki; ONO, Akifumi (Journal of Nutritional Science and Vitaminology, 1985)
After ligature of the pancreatic duct (PDL), the body weight of rats decreased for several days, but began to increase from day 7, returning to that at the time of the operation on day 14. In these PDL animals, the weight gain was not due to improved digestion resulting from duodenal leakage of pancreatic enzymes or a compensatory increase of proteolytic enzyme activities in the intestinal mucosa. There was no significant difference in pepsin activities in the gastric contents and mucosa of control and PDL rats. However, acidic proteolytic activity, with a pH range between 1 and 4 and an optimum at pH 2.8, was found to be extremely high in the intestinal contents of PDL rats. Furthermore, the intraluminal pH of PDL rats was maintained below 4.0, especially in the upper small intestine, because of the absence of pancreatic bicarbonate secretion, suggesting that compensatory digestion by acidic proteolysis accounted in part for the growth of PDL rats. The transit time of orally administered material through the gastrointestinal (GI) tract in PDL rats was longer than that in control rats on days 7 and 14. These results suggest that the weight gain of PDL rats was caused by compensatory digestion by acidic proteolysis in the small intestine and prolongation of the transit time through the GI tract.